2019
DOI: 10.1371/journal.pone.0209006
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate usage of selected antimicrobials: Comparative residue proportions in rural and urban beef in Uganda

Abstract: IntroductionIn most developing countries like Uganda, antimicrobials including β-lactams and tetracyclines are used indiscriminately in livestock. When livestock get sick and treatment is necessary, some producers and veterinarians use these drugs with minimal controls to prevent residues from occurring in the beef sent to markets. This study was done to determine the presence of drug residues above acceptable limits of two commonly used antimicrobials in Uganda’s rural and urban beef.MethodsA cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…For a clearer evaluation, all studies with salmon, other fish from aquaculture, and shrimp were combined as seafood in the evaluation, as can be seen in Figure 2 . Cattle [ 17 , 18 , 19 , 20 , 21 , 22 ], Eggs [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], Milk [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], Pork [ 58 , 59 , 60 ], Poultry [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ,…”
Section: Resultsmentioning
confidence: 99%
“…For a clearer evaluation, all studies with salmon, other fish from aquaculture, and shrimp were combined as seafood in the evaluation, as can be seen in Figure 2 . Cattle [ 17 , 18 , 19 , 20 , 21 , 22 ], Eggs [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], Milk [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], Pork [ 58 , 59 , 60 ], Poultry [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ,…”
Section: Resultsmentioning
confidence: 99%
“…A number of empirical studies on AMU in animal farming have been carried out recently in the region, but they are based on small samples and results cannot be extrapolated to the national level. Basulira et al [ 11 ], for instance, investigated AMU in beef production by studying antimicrobial residues in a sample of 134 cattle carcasses in Uganda. Manishimwe et al [ 12 ] assessed the appropriateness of AMU in Rwanda surveying 229 farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Such practices include the use of antimicrobials in feeds as growth-promoters and to prevent infections [ 51 53 ] . For instance, Basulira et al [ 49 ] reported a higher median concentration of antimicrobials such as beta -lactam antibiotics in adult carcass beef compared to young carcass beef samples. Such high levels of beta-lactam in feeds might be attributed by the indirect use of β-lactam antibiotics and tetracycline in feeds, drenches, drinking water and feed additives in the fattening systems [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Basulira et al [49] reported a higher median concentration of antimicrobials such as beta-lactam antibiotics in adult carcass beef compared to young carcass beef samples. Such high levels of beta-lactam in feeds might be attributed by the indirect use of β-lactam antibiotics and tetracycline in feeds, drenches, drinking water and feed additives in the fattening systems [49]. In the Maasai community, consumption of unboiled (raw) milk was associated with increased odds of carriage of E. coli resistant to single and multiple antibiotics [38].…”
Section: Human Practicesmentioning
confidence: 99%